2013
DOI: 10.3855/jidc.2613
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of IncF plasmids carrying beta-lactamase genes in Gram-negative bacteria from Nigerian hospitals

Abstract: Introduction: Production of beta-lactamases is the predominant cause of resistance to beta-lactam antibiotics in Gram-negative bacteria. We investigated the diversity of plasmid-borne beta-lactamase genes and replicon type of the plasmids carrying the respective genes in Gramnegative bacteria recovered from clinical infection in Nigerian hospitals. Methodology: A total of 134 Gram-negative bacteria of 13 species were analyzed for antimicrobial susceptibility, phenotypic and genotypic detection of various beta-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Recent studies reported CTX-M-type ESBLs in E. coli clinical isolates from hospitals, the community and healthy foodproducing animals in Nigeria often associated with fluoroquinolone resistance [3,4,13]. In E. coli isolates from outpatients from Southeastern Nigeria, the association of bla CTX-M-1 ESBL genes with bla TEM , bla OXA-1 and aac(6 0 )-Ib-cr genes were observed [14].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Recent studies reported CTX-M-type ESBLs in E. coli clinical isolates from hospitals, the community and healthy foodproducing animals in Nigeria often associated with fluoroquinolone resistance [3,4,13]. In E. coli isolates from outpatients from Southeastern Nigeria, the association of bla CTX-M-1 ESBL genes with bla TEM , bla OXA-1 and aac(6 0 )-Ib-cr genes were observed [14].…”
Section: Introductionmentioning
confidence: 92%
“…The increasing incidence of community-acquired infection due to ESBL-producing bacteria represents a great concern [1][2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…IncF plasmids are narrow‐host‐range plasmids that rely on both host‐encoded and self‐encoded factors for replication . They are usually large in size (>100 kb), but with low copy number and often carry an additional replicon type to initiate replication . This a strategy used by narrow‐host‐range plasmids to obtain broad‐host‐range replication.…”
Section: Plasmid Biology and Incompatibility Groupsmentioning
confidence: 99%
“…The extended-spectrum β-lactamases (ESBLs), especially those of the CTX-M type, are often associated with plasmid-mediated quinolone resistance (PMQR) and aminoglycoside resistance genes. Plasmids belonging to the IncF group have been the primary hosts for these traits (Boyd et al, 2004 ; Yao et al, 2011 ; Matsumura et al, 2013 ; Ogbolu et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%